National-to-local aid and recovery from extreme weather events evidence from the Philippines - Michael R. M. Abrigo; Arlan Brucal (Asian Development Bank (ADB), 2019)
We examine the link between extreme weather events and national aid and transfers at the municipal level in the Philippines between 1992 and 2015. Using local-level data of public income and expenditures, local precipitation, poverty incidence, and satellite-based night light luminosity, we find that the national government seems to exhibit strategic behavior by allocating more national aid and transfers during dry spells, in which damage is significantly higher and more prolonged compared to periods of higher-than-usual precipitation. Notwithstanding, the amount of national aid and transfers in these events were very small at about 2 per capita per affected municipality, suggesting that the lack of effectiveness of aid and transfers could be the result of a lack of capacity rather than poor government allocation of public funds.
Keywords: H84; O19; Q54; 330; aid and transfers; impact evaluation; natural disasters